2019
DOI: 10.1186/s13041-019-0448-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based molecular biomarkers for Alzheimer’s disease

Abstract: A major barrier to the effective conduct of clinical trials of new drug candidates against Alzheimer's disease (AD) and to identifying patients for receiving future disease-modifying treatments is the limited capacity of the current health system to find and diagnose patients with early AD pathology. This may be related in part to the limited capacity of the current health systems to select those people likely to have AD pathology in order to confirm the diagnosis with available cerebrospinal fluid and imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
201
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(203 citation statements)
references
References 81 publications
1
201
0
1
Order By: Relevance
“…Recently, several AD blood biomarkers have been developed and validated, which determine A pathology in the brain. 14,15,34,35 In a study by Nakamura et al, 16 a blood-based A biomarker showed high accuracy in predicting brain amyloid-burden; however, it should be taken into account that these results are compared only to PET imaging (AUC discovery = 0.97 and AUC validation = 0.94) and not clinical diagnosis as in this study. It is to be expected that blood biomarkers will also be tested longitudinally in large epidemiologic cohorts to assess their potential as risk factors in clinical settings and in the general population.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Recently, several AD blood biomarkers have been developed and validated, which determine A pathology in the brain. 14,15,34,35 In a study by Nakamura et al, 16 a blood-based A biomarker showed high accuracy in predicting brain amyloid-burden; however, it should be taken into account that these results are compared only to PET imaging (AUC discovery = 0.97 and AUC validation = 0.94) and not clinical diagnosis as in this study. It is to be expected that blood biomarkers will also be tested longitudinally in large epidemiologic cohorts to assess their potential as risk factors in clinical settings and in the general population.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, several AD blood biomarkers have been developed and validated, which determine Aβ pathology in the brain . In a study by Nakamura et al., a blood‐based Aβ biomarker showed high accuracy in predicting brain amyloid‐β burden; however, it should be taken into account that these results are compared only to PET imaging (AUC discovery = 0.97 and AUC validation = 0.94) and not clinical diagnosis as in this study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, concentration of CNS biomarkers outside of CSF is often extremely low, making it difficult to detect using standard assays. Other important factors complicating the analysis include peripheral expression of the protein of interest, endogenous antibodies interfering with assay results and presence of proteases which shorten the lifespan of the protein in peripheral tissues [96].…”
Section: Csf Samplingmentioning
confidence: 99%